Monitoring biofilm formation by using cyclic voltametry: effect of the experimental conditions on biofilm removal and activity - Marques, M. S. (2002)
The effect of experimental conditions on cyclic voltammetry experiments on platinum electrodes covered with biofilms formed by Pseudomonas fluorescens for 2 hours was investigated. Results show that recycling the potencial stabilizes the shape of the cyclic voltammogram after 130 cycles, but the observation of this electrode by epifluorescence microscopy showed that cells are still adhered to the platinum surface. Some experimental conditions were changed during the electrochemical measurements – sweep rate, pH of the buffer and applied potential range. Some of these parameters had a strong impact on the bacteria that are adhered to the surface, increasing the death and removal in some circumstances.